A observação da consciência de procedimentos na leitura de textos em ambiente digital - Nascimento, Marcos de Araujo (2014)
In this work aimed at examining two of the most important aspects of reading in the digital environment: 1) the awareness of the reader about the main processes involved in the accomplishment of a reading task with a specific goal and 2) the ways to develop the reading task and achieve the goal. The observation of these aspects mentioned above occured in two steps: first, each of the ten subjects of our research received two key-words to make a common search on them through the internet; then, each of the ten subjects was asked to write a report of the search and, at this point, they were asked to write, in descriptive or punctuated way, what they could remember having performed, when they were in front of the computer screen, on which a software had previously been installed to record what happened on the screen itself, and also to record the audio narrated by the subject. The core of this work considered the main types of reading and browsing behaviors, and aimed at finding out what the working memory of the reader can still keep from the procedures used when the reading task was performed, from the observation of the paths that the reader followed in the digital environment, i. e., in hypertext. In addition, a detailed survey data on procedures involving their search was presented in a written report, where an answer to the main questions concerning the processes involved, such as the awareness of the processes in pursuit of the goal of reading and the correlations between all this and the success or failure in the search, was sought. We emphasize that, as tools to get answers to these questions, we made use of the video record generated by the software, as well as the description of these videos and written accounts of the ten subjects (all of them undergraduate and graduate students from the Letters and Linguistics faculty at PUCRS). Finally, a session at the end of this dissertation was dedicated to the analyzes, correlations and conclusions about what was observed and described in the reports and records of each subject.